2018
DOI: 10.1515/aut-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of the Tendon Repair Process Using Tubular Braided Fabrics

Abstract: This paper presents the experimental and numerical analysis of the potential of a braided fabric for flexor tendon repair. Numerical models of tubular braided fabrics were generated using a python script interface and imported into ABAQUS®while Flexor tendon models were represented as silicone rubber rods. Experimental tests and Finite Element Modelling (FEM) of the flexor tendon repair was undertaken by deploying two tendon ends from opposite sides of a tubular braided fabric. This was done such that the tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The results show that the analytical equation can be used to predict the flexural bending stiffness of biaxial braided structures as shown by the close conformity of the profiles of the curves (Figure 8(b)). This was established using the RMSE (4) and MAPE (5). The data indicated that the 52.5 θ =  structure had a error margin with analytical data of RMSE 0.565 = , and MAPE 0.038 = − , this implies that the data had a better fit with the analytical data ( RMSE 0.565 = ) and also a better forecast ( MAPE 0.038 = −…”
Section: Verification Of Fe Modelsmentioning
confidence: 96%
See 1 more Smart Citation
“…The results show that the analytical equation can be used to predict the flexural bending stiffness of biaxial braided structures as shown by the close conformity of the profiles of the curves (Figure 8(b)). This was established using the RMSE (4) and MAPE (5). The data indicated that the 52.5 θ =  structure had a error margin with analytical data of RMSE 0.565 = , and MAPE 0.038 = − , this implies that the data had a better fit with the analytical data ( RMSE 0.565 = ) and also a better forecast ( MAPE 0.038 = −…”
Section: Verification Of Fe Modelsmentioning
confidence: 96%
“…Braided structures have been used in diverse fields and for myriad applications [1][2][3]. In the medical fields, stents are mainly used for support in annular structures and their potential in flexor tendon repair has been explored, [4,5]. In order to develop a braided structure suitable for possible application in tendon repair, flexural bending is a crucial deformation parameter that could be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, the helical interlacement of two sets of yarns in a circular manner occurs to produce tubular braid type textured fabric by running one set of yarns in the clockwise direction and the other in an anticlockwise direction [256]. But using 3DP technology, transversal tubular braid texture (maypole braid) simulating helical yarn configuration has been introduced [161].…”
Section: Fabric Structurementioning
confidence: 99%
“…Nevertheless, they only investigated the widthwise curling behavior of the plain knitted fabrics based on the suggested geometrical model. Further, Ochola et al have studied the repairing process of the tendon tissues by braided tubular fabrics via modeling the tubular structure [26]. However, there is only a uniaxial loading model considering the real function of the tendon.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Ochola et al. have studied the repairing process of the tendon tissues by braided tubular fabrics via modeling the tubular structure [26]. However, there is only a uniaxial loading model considering the real function of the tendon.…”
Section: Introductionmentioning
confidence: 99%